2019
DOI: 10.21608/zumj.2019.10704.11150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Bedside Lung Ultrasound Versus Chest X-Ray in Critically Ill Patients

Abstract: Background: Although chest X-ray is the main imaging approach in many settings, many limitations for it exist. Ultrasound has quite similar performances to CT with many advantages. Methods: From January 2017 till May 2018, a prospective cohort study conducted in emergency ICU at Zagazig university hospitals including 124 critically ill patients older than 18 years with respiratory distress, cough, fever, or hypoxemia. We excluded from the study pregnant females, patients with massive chest wall emphysema or he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The study reported LUS to have a higher degree of accuracy than CXR. 31 X-rays of the chest are more dangerous due to the radiation emitted to obtain the film. They are also not cost-effective, and their reliability is always in doubt.…”
Section: Cxr Vs Lus In Adults For Detecting Pneumoniamentioning
confidence: 99%
“…The study reported LUS to have a higher degree of accuracy than CXR. 31 X-rays of the chest are more dangerous due to the radiation emitted to obtain the film. They are also not cost-effective, and their reliability is always in doubt.…”
Section: Cxr Vs Lus In Adults For Detecting Pneumoniamentioning
confidence: 99%